Crecimiento y fenología de diez especies frutales amazónicas, establecidas en el Jardín Botánico de la quinta El Padmi, Zamora Chinchipe. - Medina Viñamao, Roberto Fabián (2018)
In Ecuador there are few investigations of fruit species and the loss of plant resources is high; in particular the province of Zamora Chinchipe, there is an increase in the agricultural frontier, pastures, deforestation and mining due to inefficient control; to this is added the little interest in Amazonian´s fruit species that allows to plan the production of plants in vivarium and dispose of vegetal material for projects of recovery and management of ecosystems of the region. This research has a purpose to contribute to the knowledge of the growth and phenology of ten fruit species and fulfilled with the objectives: To determine the periods of flowering and fruiting of 10 Amazonian fruit species implanted in “El Padmi” Botanical Garden and Establish the growth rates in height and diameter of 10 species of Amazonian fruit trees established in the “El Padmi” Botanical Garden. The research was developed in the Botanical Garden of “Quinta El Padmi”, property of National University of Loja, it was made the tracking of 10 species, there was used two dependent variables: flowering and fruiting; two independent variables: temperature and precipitation. The test has a block distribution, in each block a species is planted at a spacing of 4 x 4 m. The evaluation was performed every 15 days for a period of one year using binoculars x 10, the phenology was evaluated using scale the Fornier 0 absence of the phenomenon and 3 maximum presence of the phenomenon. The values were averaged from the values of each species, with the average percentages the phenological calendar was elaborated and graphically analyzed the relationship between phenology and climatic variables elaborating a “dendrofenograma”. The diameter and height measurements were performed to each individual of the 10 species, at the first month (April 2016) and at 12 months (March 2017). For the diameter, a ring was marked with red paint on the shaft at 1.30 m from the ground and measured with tape measure. The height was measured with a “hypsometer haga”. Average annual growth in diameter and height was calculated using the formula IMA = Ci-CF / n. Of the 10 evaluated species, 9 present flowering and fruiting phenophases in different months of the year with varied intensity, these were: Inga edulis (Vahl) Willd., Eugenia stipitata McVaugh., Artocarpus altilis (Parkinson) Fosberg., Pouteria caimito (Ruiz & Pav) Radkl., Pourouma cecropifolia Mart., Syzygium malaccense (L) Merr. & L.M. Perry., Rollinia mucosa (Jacq) Bail., Theobroma grandiflorum (Willd ex Sprengel) K. Schum., Borojoa patinoi Cuatrec., y Psidium guineense Sw. There is a positive relationship between precipitation increase and the beginning of the phenological phases of Inga edulis (Vahl) Willd., Eugenia stipitata McVaugh., Artocarpus altilis (Parkinson) Fosberg., Pouteria caimito (Ruiz & Pav) Radkl., Pourouma cecropifolia Mart., Syzygium malaccense (L) Merr. & L.M. Perry., Rollinia mucosa (Jacq) Bail., Theobroma grandiflorum (Willd ex Sprengel) K. Schum., Borojoa patinoi Cuatrec., y Psidium guineense Sw. The species with the best increase in forest, growth in height and IMA, are: Artocarpus altilis, Pourouma cecropiifolia, Pouteria caimito and Inga edulis, due to their rapid growth and to be heliophytic species.